Effects of Radiant Heat and Frictional Abrasion on Thermal Protective Performance of Clothing Against High Pressurized Steam. (April 2023) - He, Jiazhen; Sun, Ling; Lu, Yehu
This study focused on changes in protective performance of steam protective clothing after exposure to conditions such as thermal radiation and frictional abrasion. Totally eight radiation conditions varying on exposure duration and times, four types of abrasion scenarios with different friction cycles and three different combined treatments were designed. Results demonstrated that any increase in radiant exposure duration or exposure times would lead to an initial increase and then a following decrease in the steam protective performance. However, the steam protective performance seemed relatively immune to the friction cycles. When thermal radiation and frictional abrasion acted together, interactions between them existed and their specific interaction highly depended on the distribution of heat exposure duration and friction cycles. Findings of this study provided insight into factors influencing steam protective performance, and could be an aid in developing high performance materials or guidelines for use and maintenance of protective clothing.